Respuesta :

ANSWER

[tex]y = 3 \sin( \frac{2}{3}( x+ \frac{2}{\pi} )) - [/tex]

Or

[tex]y = - 3 \sin( \frac{2}{3}( x+ \frac{2}{\pi} )) - 1[/tex]

EXPLANATION

The general sine function is given by,

[tex]y = a \sin(bx \pm \: c) \pm d[/tex]

where

[tex] |a| = 2[/tex]

[tex]a =\pm2[/tex]

[tex] \frac{2\pi}{b} = 3\pi[/tex]

is the period.

This implies that,

[tex]b = \frac{2}{3} [/tex]

The phase shift is

[tex] \frac{b}{c} = \frac{\pi}{2} [/tex]

This implies that,

[tex]c = \frac{4}{3\pi} [/tex]

[tex]d = - 1[/tex]

is the vertical shift.

The required equation is:

[tex]y = \pm3 \sin( \frac{2}{3}( x+ \frac{2}{\pi} )) - 1[/tex]